2007
DOI: 10.1073/pnas.0609885104
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting and transmission-blocking activity of antibodies toPlasmodium falciparumelicited in mice by protein conjugates of Pfs25

Abstract: Malaria is a leading cause of morbidity and mortality, estimated to cause >1 million childhood deaths annually. Plasmodium falciparum causes the most severe form of the disease. There is as yet no licensed vaccine for this disease, despite over a half century of research. In this study, we investigated a transmission-blocking vaccine candidate, the ookinete surface protein Pfs25. Antibodies against Pfs25, drawn in during a bite, can block parasite development in the mosquito midgut, preventing transmission to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 28 publications
4
67
2
Order By: Relevance
“…The antibodies elicited by Pfs25-rEPA F1/Alhydrogel + CPG 7909 displayed almost the same activity in TBA as the antibodies elicited by Pfs25-rEPA F1/Alhydrogel. The TBA activities at 2600 units of antibody were also comparable to those previously published [6,7]. These results demonstrated that the immune sera induced by the formulation with CPG 7909 were as functional as the immune sera induced by the formulation without CPG 7909 at the same ELISA units.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The antibodies elicited by Pfs25-rEPA F1/Alhydrogel + CPG 7909 displayed almost the same activity in TBA as the antibodies elicited by Pfs25-rEPA F1/Alhydrogel. The TBA activities at 2600 units of antibody were also comparable to those previously published [6,7]. These results demonstrated that the immune sera induced by the formulation with CPG 7909 were as functional as the immune sera induced by the formulation without CPG 7909 at the same ELISA units.…”
Section: Discussionsupporting
confidence: 87%
“…Conjugation of Pfs25 to outer-membrane protein complex of Neisseria meningitidis (OMPC) greatly increased and sustained the specific antibody levels in animals [5]. Similar results were observed with the conjugation of Pfs25 to itself or to Pseudomonas aeruginosa ExoProtein A (rEPA) [6]. Our study showed that conjugation of AMA1 and Pfs25 to rEPA significantly enhanced the immune response against both malarial antigens, with a 3-fold increase for AMA1-rEPA/Alhydrogel and over a 1000-fold increase for Pfs25-rEPA/ Alhydrogel compared to unconjugated antigens [7].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…32 Furthermore, chemical conjugation of PpPfs25H-A to either ExoProtein A (EPA) of Pseudomonas aeruginosa or an outer membrane protein complex of Neisseria meningitides was shown to have a dramatically enhancing effect on both anti-Pfs25 and TB antibody responses. [13][14][15][16] Chemically conjugated Pfs25-EPA nanoparticles were subsequently manufactured under current Good Manufacturing Practices conditions and evaluated in mice in the presence of Alhydrogel, demonstrating superior immunogenicity compared with unconjugated Pfs25 plus Alhydrogel. 33 A Phase 1 clinical trial (NCT01434381) in which 30 healthy malaria-naïve adult subjects received up to three doses of the Pfs25-EPA TBV candidate (8 or 16 µg of Pfs25 at 0 and 2 mo or 47 µg of Pfs25 at 0, 2, and 4 mo) has recently been completed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, recent success has been achieved with recombinant versions of Pfs25 produced in yeast. [10][11][12][13][14][15][16][17] During the last two decades, several groups have demonstrated the potential of plants as an effective and highly scalable platform for production of recombinant vaccine antigens and therapeutic proteins (for a review see refs. 18 and 19).…”
Section: Introductionmentioning
confidence: 99%